Induction of a glibenclamide-sensitive K-current by modification of a delayed rectifier channel in rat portal vein in insulinoma cells - Edwards, G; Weston, A H (British journal of pharmacology, 1993)
In insulinoma cells (RINm5F), the glibenclamide-sensitive K-current (IK(ATP)) which developed spontaneously or after exposure to levcromakalim or to butanedione monoxime was always accompanied by a reduction in the delayed rectifier current (IK(V)). At potentials over which IK(V) was fully activated, the total outward current remained constant. In rat portal vein, the delayed rectifier channel inhibitor, margatoxin, reduced the combined induction of IK(ATP) and inhibition of IK(V) by levcromakalim. These data suggest that the ATP-sensitive K-channel, K(ATP), is a voltage-insensitive state of the delayed rectifier, KV.